Surface gloss properties of walnut tannin applied wood species - Mehmet Yaşar; Ahmet Cihangir Yalınkılıç; Alaaddin Uzun; Şadiye Yaşar (Turkish Journal of Forestry)
Nowadays, growing environmental concerns lead to studies towards more ecological and sustainable materials. This study inquiries into the effects of walnut tannin on the surface gloss characteristics of walnut (Juglans regia L.) and Scots pine (Pinus sylvestris L.) woods. For this purpose, walnut tannin was applied to the surfaces of Scots pine and walnut wood through the use of a brush, and then water-based and polyurethane varnishes were applied. To assess the visual effect of tannin application, the surface gloss of the wood samples was measured. The highest gloss value perpendicular and parallel to the fibers was obtained in the polyurethane varnished Scots pine control samples, the lowest value perpendicular to the fibers was determined in the water-based varnished walnut control samples, and the lowest value parallel to the fibers was found in the tannin + polyurethane varnished walnut. The findings demonstrate that the varnish type significantly affects the gloss values and that the walnut tannin application has a visible effect on the surface gloss properties of both wood types.